Pharmacist Led Telephonic Insulin Titration: A Pilot Study on A1C Control in a Family Medicine Residency - Raghavan P; Chamberlin S; Heidel RE; Wilson GA (Patient Related Outcome Measures)
Priya Raghavan,1 Shaunta Chamberlin,1 Robert Eric Heidel,2 Garland Anthony Wilson1 1Department of Family Medicine, UT Health Science Center Graduate School of Medicine, Knoxville, TN, USA; 2Department of Surgery, UT Health Science Center Graduate School of Medicine, Knoxville, TN, USACorrespondence: Priya Raghavan, Department of Family Medicine, UT Health Science Center Graduate School of Medicine, 1924 Alcoa Hwy, U-67, Knoxville, TN, 37920, USA, Email pvraghavan@utmck.edu